Evaluasi Rencana Pembelajaran Semester Mata Kuliah Nihonjijo Dan Seminar Desain Skripsi - Lispridona Diner (Anterior Jurnal, 2020)
The Semester Learning Plan (RPS), prepared based on current needs, we received this information from the stake holders, and also followed the demands set by UNNES itself. To find out, the RPS can be used again in the next semester, then the preparation of the RPS needs to be evaluated. The purpose of the evaluation of the RPS is to find out whether the RPS that has been prepared needs to be improved and can be used or can no longer be used in the next school year. The RPS evaluated in this article are the RPS of the thesis design seminar course, the nihonjijo course and the kaiwa chukyu kohan course. The RPS is evaluated based on KKNI and UNNES conservation values. Based on the evaluation results, the RPS of the thesis design seminar course and the kaiwa chukyu kohan course need a revision in the CPMK, UNNES conservation values are described in accordance with FBS. While the nihonjijo course needs to be revised on CPL referring to KKNI and CPMK prepared by describing the conservation values of FBS.